2017
DOI: 10.1021/jacs.6b13231
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Precision-Polyesters Enabling Optimization of Ligand–Receptor Stoichiometry for Modular Drug Delivery

Abstract: The success of receptor-mediated drug delivery primarily depends on the ability to optimize ligand-receptor stoichiometry. Conventional polyesters such as polylactide (PLA) or its copolymer, polylactide-co-glycolide (PLGA), do not allow such optimization due to their terminal functionality. We herein report the synthesis of 12 variations of the PLA-poly(ethylene glycol) (PEG) based precision-polyester (P2s) platform, permitting 5-12 periodically spaced carboxyl functional groups on the polymer backbone. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 61 publications
2
44
0
Order By: Relevance
“…(17). Use of GA-conjugated nanoparticles has significantly improved the oral bioavailability of several drugs, including cyclosporine, insulin, curcumin, and, as reported in this article, UA (17)(18)(19)46).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…(17). Use of GA-conjugated nanoparticles has significantly improved the oral bioavailability of several drugs, including cyclosporine, insulin, curcumin, and, as reported in this article, UA (17)(18)(19)46).…”
Section: Discussionmentioning
confidence: 80%
“…In brief, polymers with or without GA conjugation were first prepared. Assembly of polymers into nanoparticles and the concurrent encapsulation of UA were accomplished using the oil-in-water emulsification method (19). The amount and efficiency of UA encapsulation were determined by LC-MS. Nanoparticle particle size and shape were evaluated by dynamic light scattering and scanning electron microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory also observed that the ligand-receptor stoichiometry plays an important role in receptor-mediated drug delivery. Optimized ligand-receptor stoichiometry has been achieved through multiple coupling sites in newly formed polyester, which showed enhanced uptake and efficient drug delivery compared with benchmarking control, GA modified poly (lactic-coglycolic acid) (Ganugula, et al, 2017b). It will be interesting to see if the improved bioavailability will subsequently lead to improved clinical outcomes, in particular chronic conditions on oral dosing.…”
Section: Nanosystemsmentioning
confidence: 99%